mPGES-1-Mediated Production of PGE2 and EP4 Receptor Sensing Regulate T Cell Colonic Inflammation - Maseda, Damian; Banerjee, Amrita; Johnson, Elizabeth M.; Washington, Mary Kay; Kim, Hyeyon; Lau, Ken S.; Crofford, Leslie J. (Frontiers in Immunology, 2018)
PGE2 is a lipid mediator of the initiation and resolution phases of inflammation, as well as a regulator of immune system responses to inflammatory events. PGE2 is produced and sensed by T cells, and autocrine or paracrine PGE2 can affect T cell phenotype and function. In this study, we use a T cell-dependent model of colitis to evaluate the role of PGE2 on pathological outcome and T-cell phenotype. CD4+ T effector cells either deficient in mPGES-1 or the PGE2 receptor EP4 are less colitogenic. Absence of T cell autocrine mPGES1-dependent PGE2 reduces colitogenicity in association with an increase in CD4+RORgt+ cells in the lamina propria. In contrast, recipient mice deficient in mPGES-1 exhibit more severe colitis that corresponds with a reduced capacity to generate FoxP3+ T cells, especially in mesenteric lymph nodes. Thus our research defines how mPGES-1-driven production of PGE2 by different cell types in distinct intestinal locations impacts T cell function during colitis. We conclude that PGE2 has profound effects on T cell phenotype that are critically dependent on the microenvironment.